Characterizing the Intra-Vineyard Variation of Soil Bacterial and Fungal Communities - Liang, Hebin; Wang, Xiaowen; Yan, Junwei; Luo, Lixin (Frontiers in Microbiology, 2019)
Vineyard soil microbial communities potentially mediate grapevine growth, grape production as well as wine terroir. Simultaneously assessing shifts of microbial community composition at the intra-vineyard scale allows us to decouple correlations among environmental variables, thus providing insights into vineyard management. Here we investigated bacterial and fungal community compositions and their relationships with edaphic properties in soils collected from a commercial vineyard at four different soil depths (0-5 cm, 5-10 cm, 10-20 cm and 20-40 cm). Soil organic carbon (SOC) content, invertase activity and phosphatase activity decreased along depth gradient in the 0-20 cm soil fraction (P<0.001). The soil bacterial biomass and α-diversity were significantly higher than those of fungi (P≤0.001). Statistical analyses revealed that SOC content, pH, C/N ratio and total phosphorus (TP) were significant determinants of soil bacterial (R=0.494, P=0.001) and fungal (R=0.443, P=0.001) community structure. The abundance of dominated bacterial phyla (Proteobacteria, Acidobacteria and Actinobacteria) and fungal phyla (Ascomycota, Zygomycota and Basidiomycota) slightly varied among all soil samples. Genus Lactococcus, which comprised 2.72% of the soil bacterial community, showed increasing pattern with depth. Importantly, Candidatus Nitrososphaera, Monographella and Fusarium were also detected with high abundances in soil samples, indicating their ecological function in soil nitrogen cycle and the potential risk in grapevine disease. Overall, this work detected the intra-vineyard variation of bacterial and fungal communities and their relationships with soil characteristics, which was beneficial to vineyard soil management and grapevine disease prevention.